The Influence Of Taste And Price Perception On Onsumer Decisions In Purchasing Honda Beat Motorcycles At Dealers CV. Sinar Mas Honda - Arya Esa Kusmana; Depy Muhamad Pauzy; Suci Putri Lestari (Penerbit Jurnal Indonesia, 2022)
This study aims to determine the influence of taste and price perception on consumer decisions in purchasing Honda beat motorcycles at deales CV. Sinar Mas Honda. The method used is a quantitative approach with a reserch sample of 100 respondents from consumers of Honda Beat Motors CV. Sinar Mas Honda. The data used is primary data. The analytical tool used in this study is multiple linear regression using SPSS version 25. The results showed that the Tastes felt by consumers of Honda Beat CV. Sinar Mas Honda had very hight criteria. Price perception on consumers of Honda Beat CV. Sinar Mas Honda had very affordable criteria. Simultaneously taste and price perception have a significant influence on purchasing decisions. Partially taste has a significant influence on purchasing decisions. Partially, price perception has a significant effect on purchasing decisions.